GROWTH AND REPRODUCTION IN SOME SPECIES OF GRACILARIA AND GRACILARIOPSIS IN THE PALK BAY - Rao, M Umamaheswara (Indian Journal of Fisheries, 2011)
Growth and fruiting behaviour of the populations of Gracilaria edulis,Gracilaria foliifera and Gracilariopsis sjoestedtii are described based on the fieldstudies conducted from January 1969 to June 1971 in the Palk Bay near Rameswaram.Populations of these three agar-yielding red algae have been observedthroughout the year with two half yearly growth cycles, one from October/November to April and the other from May/June to September. The rale ofgrowth was found to vary in the growth cycles. Plants with reproductive structuresoccur in Gracilaria edulis and Gracilaria foliifera in all months of the yearand in Gracilariopsis sjoestedtii for a short period from November to March.Variations observed in the abundance of sexual, asexual and sterile plants andthe abnormal features noticed in the reproductive behaviour of these three algaehave been discussed.